Utilization of R&D Results in the Home and Foreign Plants of Multinationals - Gunnar Fors (The Research Institute of Industrial Economics (IUI), 1996)
This paper analyzes the utilization of R&D results in the home and foreign plants of Swedish multinational enterprises (MNEs). The empirical findings indicate that the firms' R&D undertaken in the home country is used as an input in both the home and foreign plants of the MNEs. Around four-fifths of the gain in value-added attributed to home R&D was realized in the MNEs' home plants, while the remaining fifth benefitted the foreign plants. Considering that the foreign plants on average accounted for a third of the MNEs' overall output, the foreign share of the gain was substantial. R&D undertaken in foreign affiliates does not appear to be used as an input in the firms' home plants.
Keywords: F23; O32; 330; R&D; Multinationals; Home and Foreign Plants